The RESPECT study: a feasibility randomised controlled trial of a sexual health promotion intervention for people with serious mental illness in community mental health services in the UK - Elizabeth Hughes; Natasha Mitchell; Samantha Gascoyne; Thirimon Moe-Byrne; Amanda Edmondson; Elizabeth Coleman; Lottie Millett; Shehzad Ali; Francine Cournos; Ceri Dare; Catherine Hewitt; Sonia Johnson; et al. (BMC, 2020)
Abstract Background People with serious mental illness (SMI) have sexual health needs but there is little evidence to inform effective interventions to address them. In fact, there are few studies that have addressed this topic for people with SMI outside USA and Brazil. Therefore, the aim of the study was to establish the acceptability and feasibility of a trial of a sexual health promotion intervention for people with SMI in the UK. Method The RESPECT study was a two-armed randomised controlled, open feasibility trial (RCT) comparing Sexual health promotion intervention (3 individual sessions of 1 h) (I) or treatment as usual (TAU) for adults aged 18 or over, with SMI, within community mental health services in four UK cities. The main outcome of interest was the percentage who consented to participate, and retained in each arm of the trial, retention for the intervention, and completeness of data collection. A nested qualitative study obtained the views of participants regarding the acceptability of the study using individual telephone interviews conducted by lived experience researchers. Results Of a target sample of 100, a total of 72 people were enrolled in the trial over 12 months. Recruitment in the initial months was low and so an extension was granted. However this extension meant that the later recruited participants would only be followed up to the 3 month point. There was good retention in the intervention and the study as a whole; 77.8% of those allocated to intervention (n = 28) received it. At three months, 81.9% (30 I; 29 TAU) and at 6 months, 76.3% (13 I and 16 TAU) completed the follow-up data collection. No adverse events were reported. There was good completeness of the data. The sexual health outcomes for the intervention group changed in favour of the intervention. Based on analysis of the qualitative interviews, the methods of recruitment, the quality of the participant information, the data collection, and the intervention were deemed to be acceptable to the participants (n = 22). Conclusions The target of 100 participants was not achieved within the study's timescale. However, effective strategies were identified that improved recruitment in the final few months. Retention rates and completeness of data in both groups indicate that it is acceptable and feasible to undertake a study promoting sexual health for people with SMI. A fully powered RCT is required to establish effectiveness of the intervention in adoption of safer sex. Study registration ISRCTN Registry ISRCTN15747739 prospectively registered 5th July 2016.